The adaptive evolution of virulence: a review of theoretical predictions and empirical tests - CRESSLER, CLAYTON E.; McLEOD, DAVID V.; ROZINS, CARLY; VAN DEN HOOGEN, JOSÉE; DAY, TROY (Parasitology, 2016)
Why is it that some parasites cause high levels of host damage (i.e. virulence) whereas others are relatively benign? There are now numerous reviews of virulence evolution in the literature but it is nevertheless still difficult to find a comprehensive treatment of the theory and data on the subject that is easily accessible to non-specialists. Here we attempt to do so by distilling the vast theoretical literature on the topic into a set of relatively few robust predictions. We then provide a comprehensive assessment of the available empirical literature that tests these predictions. Our results show that there have been some notable successes in integrating theory and data but also that theory and empiricism in this field do not ‘speak’ to each other very well. We offer a few suggestions for how the connection between the two might be improved.